In Vitro Comparison of the Effects of Two Different Acid Etchants on the Microleakage of Composite Restorations - Panahandeh, Narges; Iravani, Maryam; Halalizadeh, Zari (Journal of Dental School, 2019)
Objective: Etching of enamel and dentin is an important step in restoration of teeth with composite resin ensuring the retention of restoration and decreasing microleakage. This in vitro study sought to compare the effects of Kimiya and Etch-Rite acid etchants on the microleakage of composite restorations. Methods: This experimental study was conducted on 30 sound human molar teeth. Class V cavities were prepared on the buccal surface of teeth and the teeth were randomly divided into 2 groups of 15. Iranian acid etchant (Kimiya, Iran) was used in group 1 and Etch-Rite (Pulpdent, Watertown, MA, USA) in group 2. The teeth were restored with Valux Plus (3M, ESPE, St. Paul, MN, USA) composite resin and polished by disc. The canal apices were sealed with sticky wax and the entire tooth surface was coated with 2 layers of nail varnish except for 1 mm around the restoration margins. Specimens were immersed in 2% Fuchsin (Fuchsin Dye, Merck, Germany) for 24h and then buccolingually sectioned. Specimens were evaluated under a stereomicroscope (SF-100B, Lomo, Russia) at 40X magnification and the degree of microleakage was determined using a 0-4 scale. The degree of microleakage was statistically analyzed using Mann Whitney U test. Results: No significant difference was found between the two groups of Kimiya and Etch-Ritein the degree of microleakage at the occlusal wall (p=0.1). The degree of microleakage at the gingival wall was not significantly different between the two groups either (p=0.68). Conclusion: Based on the results, Kimiya Iranian acid etchant has an efficacy equal to that of Etch- rite.